Study on selection of a suitable material and the parameters for designing a portable flat plate base-thermal cell absorber (FPBTCA) - Muhammad Amin, Harun; Zafri Azran, Abdul Majid; Zairul Azrul, Zakaria; Ahmad Faris, Ismail; Sany Izan, Ihsan; Kamaruzzaman, Sopian; Ahmad Fadzil, Sharol; Amir, Abdul Razak (Akademi Baru, 2021)
Several types of flat plate solar collectors have been designed and developed with various technical parameters involved in the design. The inappropriate flat plate solar collector parameter design and material chosen will affect its performance. Investigation on the effect of flat plate absorber collector material, glass thickness, air gap distance, thermal cell absorber thickness, and flat plate absorber base collector thickness on the performance of solar thermal collectors was conducted in this work. The experiment was performed using the solar simulator with solar radiation of 450 and 750 W/m2. The flat plate absorber collector materials used in this experiment were stainless steel 304 and aluminum. The glass thickness used in this experiment was 2.0, 3.0, 4.0, 5.0, and 10.0 mm. The air gap between the flat plate absorber and glass used in this experiment was 0, 5.0, 10.0, 20.0, and 30.0 mm. The stainless steel thermal cell absorber thickness applied in this experiment was 0.5, 1.0, and 2.0 mm. Meanwhile, the aluminum flat plate base absorber base collector thickness was 0.5, 0.8, and 1.0 mm. The results showed that the 2.0 mm glass thickness has the maximum flat plate absorber temperature (88.1 oC at t = 600 s), high heat gain rate (0.097 oC/s), and the highest total heat gain (1207.33 J). The results also revealed that the air gap distance of 10 mm achieved the maximum flat plate absorber temperature (64.6 oC at t = 600 s), the highest heat gain rate (0.058 oC/s), and the highest total heat gain (4750.92 J). The stainless steel thermal cell absorber thickness of 1.0 mm has the thermal cell absorber temperature of 76.2 oC at t = 600 s and a high heat gain rate at 0.08 oC/s. The aluminum flat plate base absorber achieved the highest flat plate absorber temperature (67.2 oC at t = 600 s) and the highest heat gain rate (0.062 oC/s). By using double glass as glass cover increase the flat plate absorber temperature (76.3 oC at t = 600 s) and the highest heat gain rate (0.077 oC/s). This research aims to produce a flat plate absorber with better energy storage, i.e., the performance of the stainless steel plate absorber is better than aluminum with the same thickness. Although the stainless steel flat plate absorber collector showed a lower temperature than aluminum, it has a higher temperature drop than the latter.